Pilot randomized trial of selective internal radiation therapy vs. chemoembolization in unresectable hepatocellular carcinoma. (17th January 2015) - Kolligs, Frank T.; Bilbao, Jose I.; Jakobs, Tobias; Iñarrairaegui, Mercedes; Nagel, Jutta M.; Rodriguez, Macarena; Haug, Alexander; D'Avola, Delia; op den Winkel, Mark; Martinez‐Cuesta, Antonio; Trumm, Christoph; Benito, Alberto; et al.
Abstract Background & Aims To compare selective internal radiation therapy (SIRT) with transarterial chemoembolization (TACE), the standard‐of‐care for intermediate‐stage unresectable, hepatocellular carcinoma (HCC), as first‐line treatment. Methods SIRTACE was an open‐label multicenter randomized‐controlled pilot study, which prospectively compared primarily safety and health‐related quality of life (HRQoL) changes following TACE and SIRT. Patients with unresectable HCC, Child‐Pugh ≤B7, ECOG performance status ≤2 and ≤5 liver lesions (≤20 cm total maximum diameter) without extrahepatic spread were randomized to receive either TACE (at 6‐weekly intervals until tumour enhancement was not observed on MRI or disease progression) or single‐session SIRT (yttrium‐90 resin microspheres). Results Twenty‐eight patients with BCLC stage A (32.1%), B (46.4%) or C (21.4%) received either a mean of 3.4 (median 2) TACE interventions (N = 15) or single SIRT (N = 13). Both treatments were well tolerated. Despite SIRT patients having significantly worse physical functioning at baseline, at week‐12, neither treatment had a significantly different impact on HRQoL as measured by Functional Assessment of Cancer Therapy‐Hepatobiliary total or its subscales. Both TACE and SIRT were effective for the local control of liver tumours. Best overall response‐rate (RECIST 1.0) of target lesions were 13.3% and 30.8%, disease control rates were 73.3% and 76.9% for TACE and SIRT, respectively. Two patients in each group were down‐staged for liver transplantation (N = 3) or radiofrequency ablation (N = 1). Conclusions Single‐session SIRT appeared to be as safe and had a similar impact on HRQoL as multiple sessions of TACE, suggesting that SIRT might be an alternative option for patients eligible for TACE.